Pomegranate Juice Enhances Healthy Lifespan in Drosophila melanogaster: An Exploratory Study - Balasubramani, Subramani Paranthaman; Mohan, Jayaram; Chatterjee, Arunita; Patnaik, Esha; Kukkupuni, Subrahmanya Kumar; Nongthomba, Upendra; Venkatasubramanian, Padmavathy (Frontiers in Public Health, 2014)
Exploring innovative ways to ensure healthy ageing of populations is a pre-requisite to contain rising healthcare costs. Scientific research into the principles and practices of traditional medicines can provide new insights and simple solutions to lead a healthy life. Rasayana is a dedicated branch of Ayurveda (an Indian medicine) that deals with methods to increase vitality and delay aging through the use of diet, herbal supplements and other lifestyle practices. The life-span and health-span enhancing actions of the fruits of Pomegranate (Punica granatum L.), a well-known Rasayana, were tested on Drosophila melanogaster (fruitfly) model. Supplementation of standard corn meal with 10% (v/v) pomegranate juice (PJ) extended the life-span of male and female flies by 18% and 8% respectively. When male and female flies were mixed and reared together, there was 19% increase in the longevity of PJ fed flies, as assessed by MSD, the median survival day (24.8). MSD for control and resveratrol (RV) groups was at 20.8 and 23.1 days respectively. A two-fold enhancement in fecundity, improved resistance to oxidative stress (H2O2 and paraquat induced) and to Candida albicans infection were observed in PJ fed flies. Further, the flies in the PJ fed group were physically active over an extended period of time, as assessed by the climbing assay. PJ thus outperformed both control and RV groups in the life-span and health-span parameters tested. This study provides the scope to explore the potential of PJ as a nutraceutical to improve health span and lifespan in humans.